ANALISIS KINERJA LAYANAN ANGKUTAN UMUM MASSAL BUS TRANS SARBAGITA BERDASARKAN PERSEPSI KEPUASAN PENUMPANG - Dewa Made Priyantha Wedagama; Putu Alit Suthanaya; Putu Ciria Angga Pramana (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2020)
One aspect of transportation used is public transportation. It is good that public roads can affect user choices. In 2015 passengers who used Trans Sarbagita services were students and students, which was 28% of the total number of passengers. The purpose of this study is to find out how perceptions about services to public services and services of Trans Sarbagita Buses on Corridors I and II. This study uses two data techniques that are used, namely primary data consisting of data used and secondary data used to process the wrong data. Trans Transkolita that uses the results of processing questionnaires from respondents. The analytical method used is Importance Performance Analysis (IPA), Customer Service Index (CSI), and Heterogeneous Customer Satisfaction Index (HCSI). Based on the IPA analysis, almost all service attributes need to be improved, for service users' satisfaction with services obtained from the analysis using the CSI method where the current level of satisfaction of Trans Sarbagita Bus service users is 75.60% in corridor I and 80.31% in corridors II which means needing attention. From the results of HCSI the results were 38.9% corridor I and 38.1% for koriodr II, ease of reaching the Trans Sarbagita bus stop, attention of the instructor in enforcing the passengers professionally, the timeliness of the departure of the Trans Sarbagita Bus and the harmony between service hours and time which is needed by the community